Non-destructive real-time analysis of plant metabolite accumulation in radish microgreens under different LED light recipes - Garegnani, Marco; Sandri, Carla; Pacelli, Claudia; Ferranti, Francesca; Bennici, Elisabetta; Desiderio, Angiola; Nardi, Luca; Villani, Maria Elena (Frontiers in Plant Science, 2024)
The future of human space missions relies on the ability to provide adequate food resources for astronauts and also to reduce stress due to the environment (microgravity and cosmic radiation). In this context, microgreens have been proposed for the astronaut diet because of their fast-growing time and their high levels of bioactive compounds and nutrients (vitamins, antioxidants, minerals, etc), even higher than mature plants usually consumed as ready-to-eat vegetables.Our study aimed to identify the best light recipe for the soilless cultivation of two cultivars of radish microgreens (Raphanus sativus, green daikon, and rioja improved) harvested eight days after sowing, that could be used for space farming. The effects on plant metabolism of three different Light Emitting Diodes (LED) light recipes (L1-20%Red, 20% Green, 60% Blue; L2 -40% Red, 20% Green, 40% Blue; L3 -60% Red, 20% Green, 20% Blue) were tested on radish microgreens hydroponically grown. A rapid real-time non-destructive screening technique was used to characterize the altered plant metabolism with a fluorimetric device monitoring compounds such as flavonols, anthocyanins, and chlorophyll via specific fluorescence-based indices verified by standardized spectrophotometric methods. To assess plant growth morphometric parameters (fresh and dry weight, cotyledons area and weight, hypocotyl length) were analyzed. We observed a statistically significant positive effect on biomass accumulation and productivity for both cultivars grown under the same light recipe (40% Blue, 20% Green, 40% Red). We further investigated how the addition of UV and/or Far Red LED lights could have a positive effect on plant metabolite accumulation (anthocyanins and flavonols).These results are important in order to design plant-based bioregenerative life-support systems for long-duration human space exploration, with particular emphasis on the ability to use and integrate fluorescence-based non-destructive techniques to follow plant metabolite accumulation in microgreens soilless cultivation.